Effect of Family Ownership towards Tax Aggressiveness on Food and Beverages Industrial Company Listed in Indonesia Stock Exchange - Sunaryo Sunaryo (Bina Nusantara University, 2016)
The primary objectives of this research were to learn the effects of family ownership, return on assets, leverage, property plant, and equipment with tax aggressiveness, either simultaneously or partially. This research used quantitative method with secondary data collected by purposive sampling from foods and beverages industrial companies group listed in IDX and preceding journals of scientific articles research. This research used simple regression to test the hypothesis simultaneously with F test and t test for testing the partial hypothesis. Results of this research show that family ownership, return on assets, leverage, and property, plat, and equipment have affected tax aggressiveness simultaneously and significantly. The family ownership and property, plant and equipment have significant effects to tax aggressiveness, but the return on assets and leverage do not have significant effects to tax aggressiveness.